Monitoring the threatened utility of malaria rapid diagnostic tests by novel high-throughput detection of Plasmodium falciparum hrp2 and hrp3 deletions: A cross-sectional, diagnostic accuracy study - Andrea Kreidenweiss; Franziska Trauner; Miriam Rodi; Erik Koehne; Jana Held; Lea Wyndorps; Gédéon Prince Manouana; Matthew McCall; Ayola Akim Adegnika; Albert Lalremruata; Peter G. Kremsner; Rolf Fendel; et al. (EBioMedicine, 2019)
Background: Plasmodium falciparum deficient for hrp2 and hrp3 genes are a threat to malaria management and elimination, since they escape widely used HRP2-based rapid diagnostic tests and treatment. Hrp2/hrp3 deletions are increasingly reported from all malaria endemic regions but are currently only identified by laborious methodologies. Methods: We developed a novel hydrolysis probe-based, quantitative, real-time PCR (4plex qPCR) for detection and discrimination of P. falciparum infection (cytb) and hrp2 and hrp3 gene status, and to control assay validity (btub). A cross-sectional, diagnostic accuracy study was performed in Gabon for assay validation and deletion screening. Findings: In parallel to identification of P. falciparum infection in samples down to 0.05 parasites/µl, the 4plex qPCR enabled specific and valid interrogation of the parasites´s hrp2 and hrp3 genes in one go - even in low parasitemic samples. The assay was precise and robust also when performed in a routine healthcare setting in Gabon. The risk of falsely identifying hrp2 or hrp3 deletion was reduced by 100-fold compared to conventional PCR. Evaluation against microscopy was performed on 200 blood samples collected in Gabon: sensitivity and specificity of 4plex qPCR (cytb) were 100% and 80%, respectively. Stringent testing revealed hrp2 deletion in 2 of 95 P. falciparum positive and validated samples. Interpretation: The novel 4plex qPCR is sensitive, accurate and allows resource-efficient rapid screening. Monitoring and mapping of hrp2/hrp3 deletions is required to identify areas where control strategies may need to be adapted to ensure appropriate patient care and ultimately achieve malaria elimination. Funding: BMBF (03VP00402).